Diagnostic and prognostic role of the electrocardiogram in patients with pericarditis. Issue 18 (6th May 2022) - Imazio, Massimo; Squarotti, Gabriele Barberi; Andreis, Alessandro; Agosti, Alessandra; Millesimo, Michele; Frea, Simone; Giustetto, Carla; Deferrari, Gaetano Maria
Abstract : Objective: The ECG has been traditionally used to support the diagnosis of pericarditis. However, the pericardium is electrically silent and ECG changes may imply concurrent myocardial involvement rather than simple pericarditis. The aim of the present paper is to analyse the frequency, type and clinical implication of ECG changes in patients with pericarditis compared with those with myocarditis. Methods: Consecutive patients with pericarditis and/or myocarditis were included in a prospective cohort study from January 2017 to December 2020. A clinical and echocardiographic follow-up was performed at 1, 3, 6 months and then every 6 months. Cardiac magnetic resonance was used to diagnose concurrent myocarditis. Results: 166 patients (median age 47 years, 95% CI 44 to 51) with 66 men (39.8%) were included: 110 cases with pericarditis (mean age 47.7 years, 29.1% male) and 56 cases with myocarditis (mean age 44.8, 60.7% male). ECG changes were reported in 61 of 166 (36.7%) patients: 27 of 110 (24.5%) among those with pericarditis and 34 of 56 (60.7%) among those with myocarditis (p<0.0001). In multivariate logistic regression analysis, ECG changes were associated with troponin elevation (risk ratio 1.97; 95% CI 1.13 to 3.43), suggesting myocardial involvement. ECG changes were not associated with increased risk of adverse events. Conclusions: ECG changes, mainly widespread ST-segment elevation, can be recorded in about one-quarter of patients with pericarditis, and were not associated with a worse prognosis. These changes may reflect concurrent myocarditis that should be ruled out.